ANALISIS HUMAN RESOURCE DEVELOPMENT, COMMUNITY DEVELOPMENT, DAN NETWORKING, DALAM MEMPENGARUHI COMPETITIVE ADVANTIGE PERGURUAN TINGGI KEAGAMAAN ISLAM DI INDONESIA - Sutiah, Sutiah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
Today every university including PTKIN cannot avoid continually being prepared and competing with various other universities both at national and international levels. In winning the competition and replying to higher education the competitive advantage factor is taken into account. High performance of university which is based on three aspects, namely cost-based, product-based, and service-based. PTKIN must have quality and service excellence, as well as the ability to compete in the costs and excellence of majors / study programs offered. There are many factors that influence highly competitive universities, including the factors of human resource development, community development (analysis of community development) and the ability to build networks and cooperation. This study tries to annul the most dominant factors towards competitive advantage . The study took samples of Lecturers and Education Personnel at PTKIN UIN Malang, UIN Surabaya, UIN Jogjakarta, and UIN Bandung using simple random techniques. The sample of respondents is 200 people and check. Statistical analysis used multiple regression components of the Multivariate Principle. Research (1) The results showed (1) All the variables of Human Resource Development (HRD), Community Development Analysis (CDA), and Network Cooperation (NP) related to Competitive Advantage (CA) or PTKIN competitiveness (production quality), quality of service (quality of service), also competitive advantage in financing and quality of safety management (price) unless the CDA converter variable is smaller than the others. (2) HRD variable regression coefficient value of 0.714. Increasing HRD, CA will also increase by 0.714 or 71.4% of the CDA variable value of -0.168. This means, if other factors are considered constant, there is no direct effect of CDA on CA or smaller than HRD and NP because the results are -0.168. While the NP variable value is 0.409. This means, for each increase in NP, CA will also increase by 0.409 or 40.9%. (3) The results of simultaneous testing show differences in variation together between HRD, CDA, NP against CA is 75.8% or accepted 24.2% is used by other factors that are not rejected. From the results of this study, PTKIN is important for developing HR (HRD) and increasing network and quality cooperation (NP) as well as developing CDA to increase PTKIN's competitiveness towards international class or WCU (Word Class University).